Pericardial window used in the diagnosis of cardiac injury - Fraga,Gustavo Pereira (2008)
PURPOSE: The purpose of the present study is to analyze the results of subxiphoid pericardial window (SPW) and transdiaphragmatic pericardial window (TDP) procedures comparing the two techniques. METHODS: During the period of January, 1994 to December, 2004, at UNICAMP, 245 patients underwent a pericardial window (PW) procedure to evaluate the possibility of cardiac injury. We reviewed the medical records of those patients in order to compare both procedures. RESULTS: Two hundred and seven patients (84.5%) underwent the SPW procedure, and 38 (15.5%) underwent the TDP procedure. Of the patients who underwent a SPW procedure, 151 (72.9%) had gunshots injuries, and 56 (27.1%) had stab wounds. In the group of patients submitted to TDP procedure, the wound was caused by gunshot in 26 (68.4%). The SPW method has shown a sensitivity of 97.5%, specificity of 95.8%, and an accuracy of 96.1%. The TDP method demonstrated a sensitivity of 100%, specificity of 97% and a 97.4% of accuracy rate. This review showed 8 (3.3%) false positive results. There was a single case (2.6%) of complications directly associated to the TDP, and this patient developed pericarditis. CONCLUSIONS: Both techniques presented an equally great result, with high sensitivity and specificity. Both surgical techniques must be carefully done to avoid false positive results.